(untitled) (Journal of science and technology exploration, 2026)
As a core component of power batteries for new energy vehicles and energy storage systems, cathode materials play a pivotal role in determining the pace of industrial chain upgrading through their technology transfer efficiency. This paper takes Fangyuan Group as a case study to examine its approaches and outcomes in technology transfer. It identifies key challenges currently constraining Fangyuan’s scale of technology commercialization, including mismatches between production capacity and market demand, limitations inherent in its demand-driven R&D model, and insufficient talent reserves coupled with inadequate incentive mechanisms. To address these issues, the study proposes targeted optimization strategies: establishing collaborative mechanisms with research institutions and technology transfer agencies, deepening engagement with end-users, strengthening intellectual property protection, and enhancing the human resource system dedicated to technology transfer and commercialization. These recommendations aim to provide practical insights for cathode material enterprises seeking to overcome bottlenecks in technology transfer.